The Effect of Root Competition on the Growth of Sal Natural Regeneration - Bhatnagar, H. P. (Indian Forester, 1959)
The studies on root competition indicate that both trenching and weeding produce significantly different results. There is appreciable competition between sal seedlings and herbs and shrubs as well as between sal seedlings and larger trees, the former effect being much more pronounced. The growth peaks of sal seedlings occur during the periods 15th April-15 May, 15 June-15th July, and 15th August-15th September, the first and last being more important. Since during these periods the demand of actively growing sal seedlings are maximum the competition from other plants is intense. If weeding is carried out during these periods or somewhat in advance, i.e., in late winter or early summer and or in late rains, it will help to relieve the intense competition between the sal seedlings and associated flora and lead to accelerated growth of the former. The elemination of root competition from larger trees by isolating areas by digging deep trenches is impracticable. Since the effect of trenching is not very marked, the benefit will not be commensurate with the cost, even if a feasible technique were to be evolved for carrying out the operation.